Quantitative sensory profiles of upper extremity chemotherapy induced peripheral neuropathy: Are there differences in sensory profiles for neuropathic versus nociceptive pain?. Issue 1 (1st January 2019) - Hammond, Elizabeth Andersen; Pitz, Marshall; Lambert, Pascal; Shay, Barbara
ABSTRACT: Aims: The aim of this study was to define the sensory phenotypes of taxane-induced peripheral neuropathy (TIPN) between neuropathic and nonneuropathic symptoms in a breast cancer population to identify future targets for mechanism-based pain management. Methods: Participants ( n = 48) with stage I–III breast cancer. Self-report questionnaires and quantitative sensory testing were used to assess sensory symptoms. The self-report version of the Leeds Assessment for Neuropathic Symptoms and Signs (S-LANSS) divided the groups into neuropathic and nonneuropathic sensory phenotypes. In total, five visits over approximately 8 months assessed each participant from pre-chemotherapy to 6 months post-chemotherapy. Results: Out of 191 nerve assessments, 150 had an S-LANSS <12 defined as "nonneuropathic" and 41 scored >12, which was defined as "neuropathic." Numeric Pain Rating Scale (NPRS) was analyzed based on percentages of those experiencing 1+ pain (graded 1/10 or higher) versus no pain. The neuropathic group had 82.9% of 1+ pain vs. 28.7% in the nonneuropathic group (odds ratio = 7.49; 95% confidence interval, 2.76–20.3; P = 0.001). The neuropathic group reported impaired function on the Disability of the Arm, Shoulder, and Hand (DASH) questionnaire ( P = 0.002). Heat pain threshold resulted in statistical differences for the left hand but not the right hand in the neuropathic group ( P = 0.05). No other quantitative data on warm/cool or cold or vibration demonstrated sensory differences between the groups. Conclusions: Few differences in sensory profiles measured using quantitative sensory testing (QST) were found. Heat pain thresholds were normalized, possibly suggesting that the neuropathic group retained C-fiber and transient potential vanilloid 1 (TRPV1) function. Participants with neuropathic pain demonstrated significant differences with increased pain and decreased function.